(untitled) (Bangladesh Medical Journal Khulna, 2021)
Background: Intrathecal opioids enhance the duration of action of local anasthetic drugs. Both nalpuphine and fentanyl enhance the action of hyperbaric bupivacaine when introduced intrathecally as adjuvant with bupivacaine. Objective: Our study was aimed to compare the clinical efficiency of nalbuphine and fentanyl as adjuvant to hyperbaric bupivacaine for anal and perianal surgery. Methods: In this prospective randomized clinical trial patients were included from January 2007 to June 2008 at Khulna Medical College & some private clinics in Khulna. Patients were ASA (American Society of Anaesthesiology) status I & II of both gender aged 18-70 years and was randomized into two groups. Each group received either nalbuphine, (Group I) or fentanyl (Group-II) with bupivacaine. After intrathecal use every patient was examined for sensory and motor block, drug related side effects like hypotension pruritus, nausea, vomiting respiratory depression for three hours and were recorded. Results: Among two hundred study patients mean age was 49.5 and 5.2 in respective group I & II. Male female ratio was 16:14 in group I, whereas in group II it was 65:35. Mean duration of surgery was 46 and 43 minutes respectively in group I & II. Onset and cephalic extension of block was almost same in both groups. Time to recovery of sensory and motor block were significantly prolonged in Group 1. Duration of analgesia was also extended in group I. No significant drug related side effects were observed in either group. Conclusion: Nalbuphine as adjuvant to bupivacaine was clinically more efficient than fentanyl for post–operative analgesia and duration of sensory and motor block in SAB (Sub Aracnoid Block) for anal and perianal surgery. Bang Med J Khulna 2020: 53 : 27-30